2022
DOI: 10.1111/iju.15042
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of resistance to tyrosine kinase inhibitor in clear cell renal cell carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is the most common subtype of renal cell carcinoma (RCC). Loss of von Hippel–Lindau tumor suppressor gene is frequently observed in ccRCC and increases the expression of hypoxia‐inducible factors and their targets, including epidermal growth factor, vascular endothelial growth factor, and platelet‐derived growth factor. Tyrosine kinase inhibitors (TKIs) offer a survival benefit in metastatic renal cell carcinoma (mRCC). Recently, immune checkpoint inhibitors have been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 166 publications
0
8
0
Order By: Relevance
“…The process of EMT, which promotes resistance to therapy and metastases, is associated with a host of metabolic changes. Although there are no direct inhibitors to EMT, multiple metabolism-inhibiting drugs have shown indirect activity against EMT changes through various complex biochemical mechanisms [ 105 ] . There are multiple ongoing clinical trials examining the combination of these drugs with antineoplastics agents, although none of these trials include RCC patients [ 106 ] .…”
Section: Overcoming Tki Resistance In Rccmentioning
confidence: 99%
See 2 more Smart Citations
“…The process of EMT, which promotes resistance to therapy and metastases, is associated with a host of metabolic changes. Although there are no direct inhibitors to EMT, multiple metabolism-inhibiting drugs have shown indirect activity against EMT changes through various complex biochemical mechanisms [ 105 ] . There are multiple ongoing clinical trials examining the combination of these drugs with antineoplastics agents, although none of these trials include RCC patients [ 106 ] .…”
Section: Overcoming Tki Resistance In Rccmentioning
confidence: 99%
“…Additionally, TAFs may serve as a target for overcoming resistance. Histone deacetylase inhibitors offer a promising approach to diminish the activation of TAFs and eradicate their infiltration within the tumor stroma, as demonstrated by a study in patients with relapsed or refractory lymphoma or multiple myeloma [ 105 , 107 ] .…”
Section: Overcoming Tki Resistance In Rccmentioning
confidence: 99%
See 1 more Smart Citation
“…Cabozantinib was approved by the FDA for advanced RCC (2016) [ 141 ], HCC (2019) [ 142 ], and differentiated thyroid cancer (2021) [ 143 ]. It provides a substantial clinical advantage over sunitinib when used as the first-line therapy for patients with metastatic RCC [ 144 ]. Additionally, sunitinib-induced resistance can be overcome using cabozantinib in the treatment of RCC [ 145 ].…”
Section: Introductionmentioning
confidence: 99%
“…The receptor tyrosine kinase (RTK), c-Met, is overexpressed and hyper active in both clear cell and papillary RCC [ 2 , 3 ]. Upon binding with the ligand hepatocyte growth factor (HGF), c-Met activates tumor-promoting pathways and can confer therapeutic resistance in RCC [ [4] , [5] , [6] ]. In our previous studies, we found that the induction of c-Met promotes activation of the redox-sensitive transcription factor Nrf2 and over-expression of the cytoprotective molecule heme oxygenase-1 (HO-1).…”
Section: Introductionmentioning
confidence: 99%